Adequacy of an automobile manufacturer to the Brazilian standard ISO 9001:2015 - Vasconcelos, Sarah Aragão; Nunes, Deivid Marques (Brazilian Journal of Production Engineering, 2020)
For an effective performance of a company, it is appropriate to implement and adapt some standards capable of compiling and standardizing all information and processes. Therefore, the general objective of this work is to analyze the Quality Management System of an automobile manufacturer, adapting the entire company to the requirements of NBR ISO 9001: 2015 and to continuously improve this system. In order to achieve the objective, a qualitative research approach was carried out with a bibliographic, descriptive and exploratory procedure. It can be seen in the results obtained that the company standardized all departments with the tools identified at work, adapting them to the requirements of the standard and, therefore, obtained certification in the ISO 9001: 2015 standard.